2014
DOI: 10.1007/s00396-014-3345-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and self-assembly in bulk of star-shaped block copolymers based on helical polypeptides

Abstract: A series of star-shaped copolymers containing poly (styrene) (PS) and poly(γ-benzyl-L-glutamate) (PBLG) were synthesized by click reaction from alkyne-and azidefunctionalized homopolymers. The α-azide PS star-shaped homopolymer was synthesized by copper-mediated atom transfer radical polymerization from a bromine-containing star-shaped initiator, and α-alkyne PBLG homopolymers were synthesized by ring-opening polymerization of γ-benzyl-L-glutamate N-carboxyanhydride with an aminocontaining α-alkyne initiator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In the following investigations on the inner structure of TPE-PBLG 23 -based nanorods by Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD), it is confirmed that the TPE end group barely affects the conformation (α-helix, Figure S3A) of PBLG chains 52−54 as well as their alignments (hexagonal columnar arrangement, Figure S4A) in the nanorods. 55,56 To confirm the straightness of HTT aggregates retained during the SSA arrangement, the self-assembly process of TPE-PBLG 23 was monitored by TEM, dynamic light scattering (DLS), and fluorescence spectra (Figure S5). TEM studies confirmed that the straight lateral surface of nanorods is well maintained throughout the assembly process.…”
Section: Resultsmentioning
confidence: 99%
“…In the following investigations on the inner structure of TPE-PBLG 23 -based nanorods by Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD), it is confirmed that the TPE end group barely affects the conformation (α-helix, Figure S3A) of PBLG chains 52−54 as well as their alignments (hexagonal columnar arrangement, Figure S4A) in the nanorods. 55,56 To confirm the straightness of HTT aggregates retained during the SSA arrangement, the self-assembly process of TPE-PBLG 23 was monitored by TEM, dynamic light scattering (DLS), and fluorescence spectra (Figure S5). TEM studies confirmed that the straight lateral surface of nanorods is well maintained throughout the assembly process.…”
Section: Resultsmentioning
confidence: 99%
“…However, XRD patterns were clearly differentiated between these two morphologies (Figure c). Bragg peaks of the TN-PBLG nanorod at certain q values were observed (where q is the scattering vector), presenting a scattering vector ratio 1:√3:2, indicating that TN-PBLG chains in the nanorod adopt a quite symmetric type of aggregation (hexagonal columnar arrangement), , while no obvious symmetric alignment of TN-PBLG chains could be observed in the corresponding nanotoroid.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular design of block copolymers (BCs) consisting of two or more immiscible polymer segments is the focus of enormous research works in the current decade. BCs with well-defined structures and excellent control over their molecular weight and molecular weight distribution are capable of forming various ordered nanostructures in the thin films through the self-assembly of different segments. Interestingly, the BCs allow their one component to generate hexagonally packed cylinders, spheres arranged in a cubic face-/body-centered lattice, bicontinuous gyroids, or lamellar structure in the matrix of the other component. Therefore, much effort is devoted to apply these ordered nanostructures to different fields, including nanoporous membranes, nanotechnology, nanoscience, nanofilters, biomaterials, and electronic and lithographic nanotemplates. The dominant factors that govern the microphase-separated nanostructure of block copolymer are the volume fraction of different blocks, the Flory–Huggins interaction parameter, the annealing process, the order of liquid crystals, as well as the solvent used in casting and annealing procedures. However, the solvent vapor annealing (SVA) treatment is used more frequently in recent times as an alternative to thermal annealing to improve the degree of order or change the orientation of microdomains.…”
Section: Introductionmentioning
confidence: 99%